Faktor-Faktor yang Memengaruhi Kepuasan Konsumen Pengguna Handphone Merek Iphone di Kecamatan Candisari Kota Semarang - Bambang Heriawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The purpose of this study was to analyze the effect of design, features, warranty, weight, color, screen resolution, and memory on consumer satisfaction of the iPhone brand mobile phone. This study uses a quantitative descriptive research method whose conclusions are based on statistically processed figures. The population in this study were all iPhone consumers in Candisari District, Semarang City. Samples were taken as many as 100 customers. The sampling technique used purposive sampling. The data source used was primary data obtained through a questionnaire. The data analysis technique used was multiple linear regression analysis, F test, t test, and coefficient of determination test. Previously, a classical assumption test was carried out in the form of a normality test, multicollinearity test, and heteroscedasticity test. The results of the study indicate that: 1) Product attributes consisting of design, features, warranty, weight, color, screen resolution, and memory together influence consumer satisfaction of iPhone users. This is proven by the results of the F test which obtained a value of F count > F table (56.892 > 2.29) at a significance level of 5%. This means that whether consumers are satisfied or not is influenced by consumer perceptions of the characteristics of the iPhone brand cellphone product. The characteristics of the iPhone brand cellphone product sold have been able to meet consumer expectations so that consumers feel satisfied; 2) Warranty is a factor that has a dominant influence on customer satisfaction. This is proven by the results of the t test for the warranty obtaining a t count value of 4.446, higher than the t count of other variables. This means that the guarantee given by the company for the product is a factor that makes consumers feel satisfied with the product.